Decreased Serum Brain-Derived Neurotrophic Factor Concentrations 72 Hours Following Marathon Running - Roeh, Astrid; Holdenrieder, Stefan; Schoenfeld, Julia; Haeckert, Jan; Halle, Martin; Falkai, Peter; Scherr, Johannes; Hasan, Alkomiet (Frontiers in Physiology, 2021)
Background: Physical exercise has been linked to beneficial effects on brain plasticity. One potential key mechanism for this relationship is an exercise-induced increase of brain-derived neurotrophic factor (BDNF). However, the kinetics of BDNF in athletes during training phase, extreme exercise competition, and recovery period have not been investigated so far. Methods: We assessed serum BDNF concentrations in 51 marathon runners (23% female, mean age 43 years) in a longitudinal study design over a period of 6 months. Assessments were conducted during the training period before the marathon and after the marathon race during short-term (24 to 72 h) and long-term (3 months) follow-ups. Potential confounders (fitness level, sex, and platelet count) were included in subsequent linear-model analyses. Results: Linear mixed-model analyses revealed a main effect of time for BDNF concentrations over the study period (F(4,89.389) = 4.296, p = 0.003). Values decreased significantly with the lowest values at 72 h after the marathon compared to baseline (p = 0.025), a finding that was more pronounced in the larger male cohort. Conclusion: Prolonged exercise induces a significant decrease in serum BDNF concentration 72 h post-exercise. We assume that this observation is mainly driven by regenerative mechanisms and a higher muscular utilization.